The Exploration on the Energy Saving Potential of an Innovative Dual-temperature Air Conditioner and the Mechanism of the Mixed Theoretical Refrigeration Cycle - Zhao Lei; Zhao Xijin (Zhileng xuebao)
An innovative dual-temperature air conditioning system and the corresponding mixed theoretical refrigeration cycle were proposed. The new air-conditioner consists of an air handling unit and a metal radiation panel as its dual-temperature evaporators, a compressor, a condenser, two thermal expansion valves and an ejector. The state properties in the air handling process and the theoretical refrigeration cycle were analyzed and compared with those of the conventional air conditioner with fresh air. Results indicate that the coefficient of performance（COP）of the dual-temperature theoretical refrigeration cycle may be improved by 13.73% to 7.43. But the COP of the dual-temperature refrigeration cycle will drop by somewhat as the amount of fresh air required and indoor moisture increases. However, it is still greater than the COP of the conventional air conditioner by 5.21%.